Spatial and Temporal Characteristics of Precipitation and Runoff Response in Yalong River Basin - CHANG Xinyu; LIU Bin; JIA Yugong; FU Zhiyu (Renmin Zhujiang)
Under the dual influence of climate change and human activities,extreme climate occurs frequently around the world,and the precipitation in the studied basin has undergone profound changes,so it is necessary to further explore the inherent characteristics and variation laws of precipitation and runoff and thus enhance the understanding of the evolution laws of hydrological and meteorological elements in the basin under the changing environment.In this paper,Mann-Kendall nonparametric test,R/S analysis,moving t-test,and Morlet wavelet transform are introduced to analyze the interannual trend and identify abrupt changes and periodic characteristics of precipitation at meteorological stations in the Yalong River Basin in the past 50 years,and the response degree of runoff to precipitation is measured by correlation coefficient.The results show that the Hurst index of precipitation in the basin is greater than 0.5,and the precipitation trends at Qingshuihe,Shiqu,and Zhongdian stations are more significant;at the same time,due to the continuous influence of the changing environment,the precipitation in the basin has a multi-scale significant period in both time and frequency domains,and the precipitation fluctuates during small periods of 1.0~2.5 years and large periods of 4~6 years.Besides,the meteorological stations with strong runoff responses to precipitation in the basin are obtained,and the precipitation trend of other stations is not significant except Zhongdian station.The research results can provide a scientific basis for selecting driving factors of the nonlinear runoff forecasting model.